Teacher collaboration for professional learning : facilitating study, research, and inquiry communities - Lassonde, Cynthia A.; Israel, Susan E. (San Francisco : Jossey-Bass, 2009)
Teacher Collaboration for Professional Learning contains the essential information, tools, and examples teachers and school leaders need to create, manage, and sustain successful collaborative groups.
Includes bibliographical references
Keywords: Teachers -- In-service training -- United States; Teachers -- Professional relationships -- United States; Professional learning communities -- United States